Solution:
Let,
F(x)=x^3-2x-5=0
Now,
Put x=0:- 0^(3)-2*0-5= -5 (-ve)
Put x=1:- 1^(3)-2*1-5= -6 (-ve)
Put x=2:- 2^(3)-2*2-5= -1 (-ve)
Put x=3:- 3^(3)-2*3-5= 16 (+v)
Therefore the root lie between 2 and 3:
1st stage:-
Hence,
x0= 2+3/2= 5/2
x0=2.5
now,
f(x0)=2.5^(3)-2*2.5-5
f(x0)=5.625
So, the roots lie between 2 and x0(which is 2.5):
2nd stage:-
Hence,
x1= 2+2.5/2=4.5/2
x1=2.25
now,
f(x1)=2.25^(3)-2*2.25-5
f(x1)=1.89
So, the roots lie between 2 and x1(which is 2.25):
3rd stage:-
Hence,
x2= 2+2.25/2= 4.25/2
x2= 2.125
now,
f(x2)= 2.125^(3) – 2*2.125 – 5=
f(x2)=0.346
So, the roots lie between 2 and x2(which is 2.125):
4th stage:-
Hence,
x3= 2+2.125/2=2.0625
x3=2.0625
now,
f(x3)=2.0625^(3) – 2*2.0625 – 5=
f(x3)= -0.351
here, the roots lie between x2 and x3:
5th stage:-
Hence,
x4= 2.125+2.0625/2
x4= 2.093
now,
f(x4)= 2.093^(3) – 2*2.093 – 5=
f(x4)= -0.017